2019
DOI: 10.1002/cyto.a.23797
|View full text |Cite
|
Sign up to set email alerts
|

Unique Calibrators Derived from Fluorescence‐Activated Nanoparticle Sorting for Flow Cytometric Size Estimation of Artificial Vesicles: Possibilities and Limitations

Abstract: The use of high-throughput flow cytometry to characterize nanoparticles has received increased interest in recent years. However, to fully realize the potential of flow cytometry for the characterization of nanometer-sized objects, suitable calibrators for size estimation must be developed and the sensitivity of conventional flow cytometers has to be advanced. Based on the scattered signal, silica and plastic beads have often been used as flow cytometric size calibrators to evaluate the size of extracellular v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…We applied purified PICK1 to small unilamellar liposomes (SUVs), prepared from bovine brain extract (Folch fraction 1, ~2.5 µg/mL) and labeled with the lipophilic dye (DiD) followed by incubation for 1 hour (h). The distribution of fluorescence intensities of single events, representing individual liposome, was plotted using kernel density estimates (Figure 7B, grey line) and the distribution matched previously reported distributions, with the peak at log 2.4 corresponding to liposome diameters between 50 and 100 nm (35). Upon incubation with PICK1, a small but reproducible shift in the distribution towards lower intensities was observed (Figure 7B).…”
Section: The Coding Variants Alter Pick1 Fission Capacitysupporting
confidence: 77%
“…We applied purified PICK1 to small unilamellar liposomes (SUVs), prepared from bovine brain extract (Folch fraction 1, ~2.5 µg/mL) and labeled with the lipophilic dye (DiD) followed by incubation for 1 hour (h). The distribution of fluorescence intensities of single events, representing individual liposome, was plotted using kernel density estimates (Figure 7B, grey line) and the distribution matched previously reported distributions, with the peak at log 2.4 corresponding to liposome diameters between 50 and 100 nm (35). Upon incubation with PICK1, a small but reproducible shift in the distribution towards lower intensities was observed (Figure 7B).…”
Section: The Coding Variants Alter Pick1 Fission Capacitysupporting
confidence: 77%
“…Standard alternatives to silica and polystyrene beads were also introduced for EV FCM analysis. For example, liposomes or hollow organosilica beads scatter light similarly to EVs [137,138]. Also, differences in the hardware from different manufacturers can cause variabilities, which should be taken into account when comparing data from different flow cytometers [131].…”
Section: Fcmmentioning
confidence: 99%
“…First, we used a commercially available calibration bead mixture called Gigamix, which contains beads with different well-defined diameters ranging between 100 nm and 900 nm and inserted the gate in a way to identify particles ranging between 100 nm and 500 nm. This method is generally accepted, 28,29 although recently its accuracy has been questioned, 1,30 since synthetic solid beads and biological vesicles have different refractive indices (e.g., 200 nm EVs scatter 40-300-fold less light than 200 nm polystyrene beads at a wavelength of 405 nm) for which reason polystyrene beads cannot be used directly for the sizing of EVs. 31,32 Chandler et al demonstrated that 400 nm polystyrene beads likely correlate with 1,000 nm microparticles.…”
Section: Discussionmentioning
confidence: 99%